Highly Conserved Evolution of Aquaporin PIPs and TIPs Confers Their Crucial Contribution to Flowering Process in Plants - Li, Qi; Tong, Tao; Jiang, Wei; Cheng, Jianhui; Deng, Fenglin; Wu, Xiaojian; Chen, Zhong-Hua; Ouyang, Younan; Zeng, Fanrong (Frontiers in Plant Science, 2022)
Flowering is the key process for the sexual reproduction in seed plants. In gramineous crops, the process of flowering, which includes the actions of both glume-opening and glume-closing, is directly driven by the swelling and withering of lodicules due to the water flow into and out lodicule cells. All these processes are considered to be controlled by aquaporins, which are the essential transmembrane proteins that facilitate the transport of water and other small molecules across the biological membranes. In the present study, the evolution of aquaporins and their contribution to flowering process in plants were investigated via an integration of genome-wide analysis and gene expression profiling. Across the barley genome, we found that HvTIP1;1, HvTIP1;2, HvTIP2;3 and HvPIP2;1 were the predominant aquaporin genes in lodicules and significantly up-regulated in responding to glume-opening and -closing, suggesting the importance of them in flowering process of barley. Likewise, the putative homologs of the above four aquaporin genes were also abundantly expressed in lodicules of the other monocots like rice and maize and in petals of eudicots like cotton, tobacco and tomato. Furthermore, all of them were mostly up-regulated in responding to the process of floret opening, indicating a conserved function of these aquaporin proteins in plant flowering. The phylogenetic analysis based on OneKP database revealed that the homologs of TIP1;1, TIP1;2, TIP2;3 and PIP2;1 were highly conserved during the evolution, especially in the angiosperm species, in line with their conserved function in controlling flowering process. Taken together, it could be concluded that the highly evolutionary conservation of TIP1;1, TIP1;2, TIP2;3 and PIP2;1 plays important roles in the flowering process for both monocots and eudicots.